Penerapan Model Psikoedukasi untuk Meningkatkan Pengetahuan Masyarakat Gading Rejo Timur dalam Pemberantasan Sarang Nyamuk(PSN) - Siti Maesaroh; Doni Faizal; Fella Rahmawati; Adinda Puspa Dewi; Tica Finanda; Maulida syifa Azizah; Ronal Prayoga; Nuri Mardiah Munawaroh; Khoirunnisa Kesumayuda (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service was conducted as a form of field activity program. Dengue Hemorrhagic Fever (DHF) remains a serious global and national health threat, with more than 131,000 cases recorded in Indonesia in 2025. Although government programs have been implemented, the gap between public knowledge and actual preventive actions in the field remains a major challenge. This study aimed to evaluate the effectiveness of a psychoeducation model in improving community understanding of Mosquito Nest Eradication (PSN) in Dusun Dua, Pekon Gading Rejo Timur. Using an experimental design, this activity involved 15 participants through three stages: initiation, interactive socialization, and the use of visual educational media. The results showed a very significant increase in knowledge. Pre-test scores (5–8) increased sharply to post-test scores (11–14), with 70% of participants achieving near-perfect scores. The highest increase recorded was 9 points. It can be concluded that the educational intervention proved effective. However, this success needs to be followed up by consistently strengthening community participation to transform knowledge into sustainable preventive behavior in order to reduce future DHF fatality rates.